Timing of the Matuyama–Brunhes geomagnetic reversal: Decoupled thermal maximum and sea-level highstand during Marine Isotope Stage 19. (5th October 2015) - Hyodo, Masayuki; Kitaba, Ikuko
Abstract: Recent high-resolution magnetic and microfossil data from a long core penetrating the Osaka Group, Japan are astronomically tuned and reassessed to reveal detailed stratigraphic features across the Matuyama–Brunhes (MB) polarity transition during Marine Isotope Stage (MIS) 19. The sediments have a uniform and high average accumulation rate of 63 cm/ky. Astronomical tuning based on six calibration points, including a clear MIS 19.2 sea-level lowstand, dates the main MB boundary (MBB) to 777.6 ka, the sea-level peak of the MIS 19.3 highstand to 780.7 ka, and the climatic thermal maximum (TM) to 776.4 ka. The MB transition began with a short-lived normal polarity episode that occurred before the highstand at MIS 19.3, and terminated with multiple rapid reversals that occurred between highstand MIS 19.3 and lowstand 19.2. The TM just postdates the termination of the MB transition, and occurs about 4000 years after the sea-level peak. The delayed TM is also observed at Gesher Benot Ya'aqov, Israel and on the Mediterranean coast, and possibly at Lake Baikal. In high-resolution records from Chinese loess–paleosols and deep-sea sediments, the rapid reversal zone of the MBB has a very similar climatostratigraphic character. These magneto-climatostratigraphic features in MIS 19 are useful for correlating between terrestrial and marine sediments. The delay in warming relative to the sea-level highstand seems to have been due to a cloud-albedo effect induced by an increase in galactic cosmic ray flux during an extremely low magnetic field intensity interval.